2010
DOI: 10.3997/1873-0604.2010055
|View full text |Cite
|
Sign up to set email alerts
|

Relative hydraulic conductivity and effective saturation from Earth’s field nuclear magnetic resonance – a method for assessing the vadose zone

Abstract: Beside the water content, petrophysical nuclear magnetic resonance (NMR) techniques in the lab and in boreholes as well as in the field, provide estimates of the hydraulic conductivity of water saturated sediments and rocks. In the vadose zone, the hydraulic conductivity is a function of the water saturation. Regarding the characterization of the vadose zone, the magnetic resonance sounding (MRS) method is expected to have great potential. However, so far, the petrophysical relationship of the hydraulic proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 28 publications
4
18
1
Order By: Relevance
“…While the literature on NMR measurements of water‐saturated materials is extensive, there are only a limited number of studies that focus on the interpretation of NMR measurements for applications in the vadose zone. Such studies have shown that the T2‐distribution, via its relation to the PSD, can be used to estimate the water retention curve (e.g., Costabel and Yaramanci ; Costabel and Yaramanci ; Jaeger et al . ); however, this interpretation requires that the NMR measurement be collected on a fully saturated sample and that relaxation occurs in the fast diffusion regime.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the literature on NMR measurements of water‐saturated materials is extensive, there are only a limited number of studies that focus on the interpretation of NMR measurements for applications in the vadose zone. Such studies have shown that the T2‐distribution, via its relation to the PSD, can be used to estimate the water retention curve (e.g., Costabel and Yaramanci ; Costabel and Yaramanci ; Jaeger et al . ); however, this interpretation requires that the NMR measurement be collected on a fully saturated sample and that relaxation occurs in the fast diffusion regime.…”
Section: Introductionmentioning
confidence: 99%
“…). Because of this relation, a number of studies have successfully estimated the unsaturated hydraulic conductivity and the water retention curve for unsaturated, unconsolidated materials (Bird and Preston ; Costabel and Yaramanci ; Costabel and Yaramanci ; Chen, Liaw, and Watson ; Ioannidis et al . ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach was verified for glass beads by Ioannidis et al . [2006] and for sand of different grain sizes by Costabel and Yaramanci [2011b]. …”
Section: Introductionmentioning
confidence: 99%
“…We focused on the upper part of the soundings (depth <25 m and pulses <2500 A: ms) because of the best resolution, and these depths/pulses values are reached by all soundings. The relaxation time T Ã 2 ðe max Þ associated with maximum signal amplitude characterizes the lithological properties of the rock (including possible alteration and clay infilling) because the relaxation measured in a specific pore space always decreases with its saturation degree as shown in recent laboratory (e.g., Ioannidis et al, 2006;Boucher et al, 2011;Costabel and Yaramanci, 2011;Mohnke et al, 2015) and field studies (e.g., Costabel and Gunther, 2014;Walsh et al, 2014). On the other hand, θ Further investigation of the relationship between MRS water storage and flow factors, such as those used in vulnerability approaches is hindered by (1) the number of soundings performed, which does not permit statistical analyses such as principal component analysis, and (2) the uncertainty regarding MRS results, which is in part due to equivalency issues in the inversion of the MRS signal.…”
Section: Hydrogeological Interpretation and Consistency Of Mrs Water mentioning
confidence: 98%